Analisis Campur Kode dan Alih Kode Percakapan Acara Bazar Sekolah - Retna Ningsih (Peneliti.net, 2022)
The use of code switching and code mixing is a symptom of language that occurs in a society that is rich in language. The language used varies. This research was carried out at Yadika Middle School, West Jakata. This study uses a qualitative method . This method describes code switching and code mixing from students and teachers as well as the community around SMP Yadika 5 West Jakarta. Respondents consisted of 15 students and 6 teachers. In this study, data analysis was carried out using qualitative descriptive analysis. The researcher uses the listen, note, and record method because the researcher hears, listening and recording conversations according to the methodology used in the study. The results of the study show that code switching and code mixing occur or change in Indonesian into regional languages ​​or vice versa. The emergence of code switching and code mixing is caused by the speaker's dialect, and wants to close the distance between the seller and the buyer.